Synthesis and Characterization of α-Fe2O3 Nanoparticles Prepared by PLD at Different Laser Energies - Jihad, Ghaith H. (Iraqi Journal of Science, 2021)
In this paper, ferric oxide nanoparticles) Fe2O3 NPs( were synthesized directly on a quartz substrate in vacuum by pulse laser deposition technique using Nd:YAG laser at different energies (171, 201,363 mJ/pulse). The slides were then heated to 700o C for 1 hour. The structural, optical, morphological, and electrical properties were studied. The optical properties indicated that the prepared thin films have an energy gap ranging from 2.28 to 2.04 eV. The XRD results showed no lattice impurities for other iron oxide phases, confirming that all particles were transformed into the α-Fe2O3 phase during the heating process. The AFM results indicated the dependence of nanoparticles size on the laser energy. As the laser energy increased, the average grain size increased from 72.6 nm to 79.02 nm. Hall effect measurement indicated that the film was an n-type semiconductor.